Presence of crevicular fluid Prostaglandin E2 in relation with clinical and radiographic periodontal status - Javier Elpidio Monzón; Rolando Pablo Juarez; Miguel Jorge Acuña; Carlos Rubén Caramello (Universidad Nacional de Colombia, 2016)
Background and Objectives: Prostaglandin E2 (PGE2) is present in gingival crevicular fluid the (GCF) and is evidenced in periodontal disease (PD). However, there are no enough reports to correlate the PGE2 concentrations in GCF in periodontal health and disease with clinical and radiographic indicators, age and gender. Hence, the present study is aimed to estimate the levels of PGE2 in GCF of subjects without periodontal disease (SEP) and periodontal disease (CEP). Materials and Methods: 99 subjects were selected, 33 without PD (G1) and 66 with PD, 33 with gingivitis (G2) and 33 with periodontitis (G3), which were submitted to a clinical and radiographic diagnosis, registering samples FGC, being stored, centrifuged and refrigerated for preservation. Subsequently the concentration of crevicular PGE2 was measured by using the enzyme linked immunosorbent assay (ELISA), determining the concentration of each subject. Results: PGE2 was detected in all the samples. The G1 presented a concentration of 28.82 ± 2.88 pg / mL, G2 44.91 ± 4.37 pg / mL and G3 148.67 ± 74.74 pg / mL (p <0.0001). PGE2 levels were significantly correlated with bleeding on probing, probing depth, attachment loss and bone loss (p <0.05). PGE2 levels were modified by age, but not gender. Conclusion: It is well known that activated inflammatory cells produce inflammatory mediators that stimulate the production of PGE2. The findings of this study demonstrate an increased concentration of PGE2 in FCG according to the presence of greater severity of PD. PGE2 may be considered as a biomarker in PD progression. However, controlled, longitudinal studies are needed to confirm this possibility.